2017
DOI: 10.1080/16549716.2017.1356641
|View full text |Cite
|
Sign up to set email alerts
|

Comparing performance of methods used to identify pregnant women, pregnancy outcomes, and child mortality in the Iganga-Mayuge Health and Demographic Surveillance Site, Uganda

Abstract: Background: In most low and middle-income countries vital events registration for births and child deaths is poor, with reporting of pregnancy outcomes highly inadequate or non-existent. Health and Demographic Surveillance System (HDSS) sites and periodic population-based household-level surveys can be used to identify pregnancies and retrospectively capture pregnancy outcomes to provide data for decision making. However, little is known about the performance of different methods in identifying pregnancy and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 18 publications
1
20
0
Order By: Relevance
“…Our analysis covers data from eight sites in six countries, including Kersa and Harar in Ethiopia; Dar es Salaam and Dodoma in Tanzania; Ningo Prampram in Ghana, Ibadan in Nigeria; Iganga and Mayuge in Uganda; and Nouna in Burkina Faso. Study site details are described in Berhane et al and other studies .…”
Section: Methodsmentioning
confidence: 99%
“…Our analysis covers data from eight sites in six countries, including Kersa and Harar in Ethiopia; Dar es Salaam and Dodoma in Tanzania; Ningo Prampram in Ghana, Ibadan in Nigeria; Iganga and Mayuge in Uganda; and Nouna in Burkina Faso. Study site details are described in Berhane et al and other studies .…”
Section: Methodsmentioning
confidence: 99%
“…Prospective data on pregnancies and their outcomes were collected between 2006 and 2010 through routine surveillance in the HDSS. In 2011, a cross-sectional pregnancy history study was conducted amongst 10,540 women aged 15–49, and details are reported elsewhere ( 16 ). Village-based scouts notified verbal autopsy interviewers of deaths, including maternal deaths, stillbirths, and neonatal deaths, as they occurred.…”
Section: Methodsmentioning
confidence: 99%
“…The approximately 25 000 registered adolescents aged 10‐19 make up one‐third of the total population. Twice per year, trained field workers record births, deaths, pregnancies and in‐ and out‐migrations . IMHDSS records were used to select a random sample of adolescents stratified by urbanicity.…”
Section: Communities and Sampling Proceduresmentioning
confidence: 99%